Wittgenstein and metamorphoses of legal language - A. B. Didikin (Омский научный вестник: Серия "Общество. История. Современность")
The paper analyzes the evolution of Wittgenstein’s philosophical ideas and the influence of his views on the analytical legal philosophy and the legal language theory. Based on the key arguments of the «Logical-philosophical Treatise», the author reconstructs the possibility of displaying legal phenomena in the legal language from the position of logical validity and the relationship between the syntax and semantics of normative prescriptions. Modern discussions about the possibilities of implementing Wittgenstein’s arguments about the rule following problem and the skeptical argument in the field of interpretation and clarification of the content of legal norms are considered. The concepts of D. Patterson and A. V. Nekhaev on the social context of interpretation of judicial practice and the motives of judges in making legal decisions are analyzed. The author substantiates the position on the deep relationship between every day and professional discourses in the legal language